A religiosidade em “Adão no éden” de Carlos Fuentes (Comunicaciones en Humanidades, 2017)
Resumo: Este artigo busca analisar a religiosidade no livro Adão no Éden de Carlos Fuentes, escritor mexicano, que trata de maneira simples as questões frágeis da América Latina, fazendo denúncias das suas políticas arcaicas e sociais que se mantêm imutáveis. Toca nas feridas ainda abertas, tanto do México quanto da América Latina, como a religião, que é usada para manipular o povo cobrindo o uso do poder abusivo de líderes que deveriam defender a segurança do país.Abstract: This paper aims to analyse the religious inssues presented on the book “Adão no Éden”, by Carlos Fuentes, a Mexican writer. It is breefly announced the sensitive issues round Latin America, making denounces of the archaic politics and social matters that remain unchangeable in its society. To go further in his denoucement, the author also highlights how religion is used in Mexico and all over Latin America as well to manipulate people concerning the use of abusive power of leaders who should defend the country’s security somehow.